Ethnic and migration-related inequalities in health anxiety: A systematic review and meta-analysis - Barbek, Rieke; Henning, Sinje; Ludwig, Julia; von dem Knesebeck, Olaf (Frontiers in Psychology, 2022)
Background: Health anxiety exists on a continuum ranging from the absence of health awareness to the obsessive fear of having a serious illness despite reassurance. Its pathological manifestation can be diagnosed as hypochondriacal or illness anxiety or somatic symptom disorder. Health anxiety is associated with psychological distress and adverse life events, among others, and leads to considerable economic burden. Compared to the majority population, migrants and ethnic minorities often face major health inequalities. Several mental illnesses and psychosomatic complaints are more common among these groups. To date, potential ethnic and migration-related inequalities in health anxiety have not been clearly described. However, they are of high relevance for the provision of adequate health care of this diverse and potentially vulnerable group. Thus, we conducted a systematic review and meta-analysis of health anxiety in migrants and ethnic minorities. Methods: A systematic literature search of PubMED, Web of Science, PsycINFO, and PSYNDEX was conducted, covering all studies published until 1st of December 2021. Studies were selected if they employed validated measurement tools of health anxiety and examined migrants and/or ethnic minorities in comparison with the majority population. Meta-analytic methods were applied by using a random-effect model. The study quality was assessed with the Effective Public Health Practice Project Quality Assessment Tool (EPHPP). Results: We identified 18 studies from 445 studies initially screened. Of these, 14 studies conducted in North America with a total number of 5,082 study participants were included in the meta-analysis. The pooled effect size indicated a higher risk of health anxiety in migrants and ethnic minorities compared to the majority population (OR 1.39, 95%-CI 1.01 to 1.92). The results proved not to be robust according to publication bias (adjusted OR 1.18, 95%-CI 0.83 to 1.69) and fail-safe N (2/3 < benchmark N=75) and are limited due to heterogeneity (I²=57%), small sample sizes and an overall low quality of included studies. Conclusion: To address the diversity of migrants and ethnic minorities, intersectional approaches across different countries are needed in research to shed further light on social inequalities in health anxiety linked to migration. Registration: PROSPERO registration number CRD42022298458.